The Movement of Family Empowerment through Bridal Post Program Against Stunting Prevention in Iloponu Village, Gorontalo Regency - Lisda Van Gobel; Sofyan Alhadar; Misbahudin Djaba; Iin Laki (Asian Journal of Community Services, 2022)
The purpose of the service activity is to prevent the number of stunting cases in Gorontalo Province, especially in Iloponu Village, Tibawa District, Gorontalo Regency. There are several methods used in the form of socialisation and direct assistance. The timing of the implementation of this activity will be carried out in August 2022. Based on the findings in this activity, there were 17 cases of stunting in Iloponu Village. This is updated by the economic level of the community which is still at a low level so that parents have not been able to provide nutritious food to children. In addition, the level of education of parents is also one of the factors in the emergence of stunting cases in Iloponu Village. It can be concluded that Stunting is a chronic disease that can interfere with the growth of children whose effects can penetrate into a person's career if prevention is not carried out early.